Development of guidelines for earthquake resilient non-engineered construction for the Philippines - Reyes, John Paolo R.; Germar, Fernando J.; Aquino, Diocel Harold M. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
The aim of the research is to be able to provide basic information and tools to foremen, masons and carpenters who build houses without the help of qualified professionals like engineers and architects in its design and construction. A simplified manual for laymen was developed to help achieve better seismic performance of non-engineered reinforced concrete frame with masonry infill wall residential structures. The guideline was developed by identifying typical damages experienced by RC residential structures during an earthquake and compiling standards and codes, both local and international, as well as best practices already established in the country. Problematic areas in practices for local non-engineered construction contributing to the dismal seismic perfonnance of RC residential structures were also identified to supplement the vulnerabilities found in this type of construction system . Expert opinion is recommended to be sought to further validate the reliability of the manual and assess its effectiveness as a guide for the construction of non-engineered houses.
Gabay sa paggawa ng mas pinatibay na bahay laban sa lindol para sa mga foreman, mason at karpintero.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Earthquake resistant design -- Philippines; Earthquake resistant design -- Standards; Buildings -- Earthquake effects; House construction -- Amateurs' manuals